$\unicode[STIX]{x1D6E5}$-CONVERGENCES OF WEIGHTED AVERAGED PROJECTIONS IN $\text{CAT}(\unicode[STIX]{x1D705})$ SPACES. (14th June 2021) - CHOI, BYOUNG JIN
Abstract: We first introduce the weighted averaged projection sequence in $\text{CAT}(\unicode[STIX]{x1D705})$ spaces and then we establish some inequalities for the weighted averaged projection sequence. Using the inequalities, we prove the asymptotic regularity and the $\unicode[STIX]{x1D6E5}$ -convergence of the weighted averaged projection sequence. Furthermore, we prove the strong convergence of the sequence under certain regularity or compactness conditions on $\text{CAT}(\unicode[STIX]{x1D705})$ spaces.